Thermo‐Responsive MOF/Polymer Composites for Temperature‐Mediated Water Capture and Release. Issue 27 (24th March 2020) - Karmakar, Avishek; Mileo, Paulo G. M.; Bok, Ivan; Peh, Shing Bo; Zhang, Jian; Yuan, Hongye; Maurin, Guillaume; Zhao, Dan
Abstract: We report an in situ polymerization strategy to incorporate a thermo‐responsive polymer, poly( N ‐isopropylacrylamide) (PNIPAM), with controlled loadings into the cavity of a mesoporous metal–organic framework (MOF), MIL‐101(Cr). The resulting MOF/polymer composites exhibit an unprecedented temperature‐triggered water capture and release behavior originating from the thermo‐responsive phase transition of the PNIPAM component. This result sheds light on the development of stimuli‐responsive porous adsorbent materials for water capture and heat transfer applications under relatively mild operating conditions. Abstract : Water, water everywhere : In situ polymerization is used to prepare thermo‐responsive PNIPAM@MIL‐101(Cr) composites with up to 440 wt % of water uptake capacity from humid air at 96 % RH and 25 °C. The hydrophilic‐to‐hydrophobic phase transition of the PNIPAM component promotes 98 % of captured water being released at a mild condition of 40 % RH and 40 °C.